Shame! Rearming, Refiguring and Transfiguring - del Pozo Barriuso, Diego (Re-visiones, 2024)
This text highlights the importance of managing the passions, affections and emotions in neoliberal Fear politics. Thanks to the thinking of Sara Ahmed who analyses how today the workings of emotions are economic, talking about „affective economies.“ The production model of the emotions of Ahmed puts forward a critique of the privatisation and the psychologising of emotions, given that emotions are performative in their circulation. Returning to the idea of affect of shame as a transformational performance of Eve Kosofky Sedgwick, the text also explores the performative potential that can be deployed in a process of collectivisation of shame against the neoliberal politics of fear and hate whether that be in the context of activism, contemporary art or the production of images.